Determining the criteria of choosing tour packages in Langkawi Island using FAHP / Ku Auni Dalili Ku Zahrin ... [et al.] - Ku Zahrin, Ku Auni Dalili; Ab Halim, Huda Zuhrah; Mohd Idris, Mohd Fazril Izhar; Fauzi, Nur Fatihah; Ahmad Bakhtiar, Nurizatul Syarfinas; Khairudin, Nur Izzati (UiTM Cawangan Perlis, 2022)
Malaysia enters the endemic phase of Covid-19 on 1st April 2022. Since then, the Malaysia's economy has started to recover, and domestic tourism has also restarted. Tourism is one of the factors that contributed to the economy. Avoiding the headache to plan their own trips, tourists usually count on tour operators to turn their dream vacations into realities. Booking a tour is the easiest way for a traveller to experience a foreign land and at the same time they could enjoy their vacation and visit the best spots. The main objective of this study is to determine the main criteria of a tour packages in Langkawi Island by using Fuzzy Analytical Hierarchy Process (FAHP). The five criteria identified are transportation, cost, food service, accommodation, and tour guide. Results showed that the transportation is the most important criteria a tourist look forward in the selection of a tour package.